Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Show that

$\displaystyle e^x=I_0(x)+2\sum_{n=1}^\infty I_n(x)$

Using the following expansion

$\displaystyle e^{i\rho\cos \varphi}=\sum_{m=-\infty}^{\infty}J_m(\rho)[ie^{i\varphi}]^m$ with $\varphi=0 , \rho = -ix$

share|improve this question
    
In homework-type problems, you should first give your own attempts and thoughts. –  GEdgar Jun 12 '13 at 0:35

1 Answer 1

Split $\displaystyle e^{i\rho\cos \varphi}$ into real and imaginary parts, and using the relations here, the fact that $J_{2n}(-ix) = J_{2n}(ix) = i^{2n} I_{2n}(x)$, $J_{2n-1}(-ix) = -J_{2n-1}(ix) = -i^{2n-1} I_{2n-1}(x)$ and substituting $\rho = -ix$ and $\varphi = 0$ we get:

$\cos(\rho\cos(\varphi)) = \cosh(x) = I_0(x) + 2\sum_1^{\infty}(-1)^ni^{2n}I_{2n}(x)$.

and

$i\sin(\rho\cos(\varphi)) = \sinh(x) = 2\sum_1^{\infty}(-1)^{n}i^{2n}I_{2n-1}(x)$.

Summing the two and the result $\displaystyle e^x=I_0(x)+2\sum_{n=1}^\infty I_n(x)$ follows.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.